Adsorption dynamics and mechanism of aqueous sulfachloropyridazine and analogues using the root powder of recyclable long-root Eichhornia crassipes. (April 2018) - Liu, Lin; Hu, Shuangqing; Shen, Genxiang; Farooq, Usman; Zhang, Wei; Lin, Sen; Lin, Kuangfei
Abstract: In this study, we reclaimed the root powder of long-root Eichhornia crassipes ( L.R.E.C. ) as a biosorbent to remove aqueous sulfachloropyridazine (SCP) and other sulfonamides. The adsorption processes were investigated dependent on multiple measurements, including FT-IR and XPS analysis. The results confirmed that the basic amine group of neutral SCP molecules and the carboxyl hydroxyl on the surface of the root powder played the leading role in adsorption processes. Additionally, the experiments of ionic strength effect validated the involvement of electrostatic interaction in adsorption. Meanwhile, the adsorption data were fitted by various models and the results indicated that the Pseudo-second-order model and Freundlich model could well describe the adsorption processes, indicating the existence of physisorption and chemisorption as multi-layer adsorption. The maximum capacities of root powder for SCP were calculated to be 226.757 μg g −1 (288.15 K), 182.815 μg g −1 (303.15 K) and 163.132 μg g −1 (318.15 K) at pH of 3.0. The thermodynamic results revealed that the adsorption was a spontaneous and exothermic process. Moreover, the accordance with intra-particle diffusion presented that the adsorption processes could be divided into three steps and the reaction constant had a negatively linear relationship with the thickness of the boundary layer. The results proved that root powder of L.R.E.C. has great potential to remediate sulfonamides at practical level. Graphical abstract: Image 1 Highlights: Root powder of long-root Eichhornia crassipes could well adsorb sulfonamides. Solution pH resulted in a significant effect on SCP and other sulfonamides removal. Sorption was generally governed by Lewis acid base interaction and electrostatic interaction. Both kip and the thickness of boundary layer had a linear negative relationship.